(3GdSjQI GdfHhjI hcJGH GdeZGRis - (3eMeO Hf ESMGb Hf jSGQ GdeWdHj HGdhdGA, GdeOfj,J (B151 (3g` s
(3ChdgG (B:s
(3MOjK HMjQ GdQGgH CNHQfG GdTjN CHh GdMSjf CMeO Hf eMeO Hf GdfbhQ CeQ QShd Gddg Udi Gddg Ydjg hSde Gdjg HYO LOg s
(3BNQgG (B:s
(3jfJgi CKfGA bUI ESdGe LQjQ Hf YHO Gddg QVi Gddg Yfg s
(3QhGjI jhfS Hf HcjQ GdeJhai SfI (B199s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B28s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJGQjNs